Resolvability of the public dental service in a municipality in the State of Bahia, Brazil (Research, Society and Development, 2022)
Objective: This study aimed to verify the dental procedures offered by the public network and characterize the resolvability of primary health care in a municipality in Bahia. Methods: This is a descriptive cross-sectional study with data collected in the Health Information System for Primary Care in the year 2019. Data were collected regarding gender, age group, types of procedures performed in primary care, first programmatic dental appointment and the completed treatments. The indicator of proportion of tooth extraction in relation to individual clinical procedures and the indicator of resolution were used. Results: The results showed that the municipality's dental services were more used by women (62.94%) and by the age group from 0 to 19 years (26.24%). Dental procedures in the basic periodontics group were the most performed (45.54%) and there was a high proportion of extractions in relation to individual clinical procedures (11.14%). It was found that the municipality's oral health service had high resolvability (86.67%), demonstrating that most of the treatments initiated were able to be completed. Conclusion: The municipality had a high rate of resolvability for dental services in primary care in the period studied. The indicators adopted in the study can help in the implementation of actions that promote an improvement in the quality of the oral health service and that meets the health needs of the population.